Paedagogica historica, quo vadis? An epilogue on the ambivalences and paradoxes of doing educational history. (2nd November 2022) - Depaepe, Marc
ABSTRACT: The present epilogue, concluding a special issue on the development of our field in lesser-known geographical contexts, takes the opportunity to air some of the author's personal views. After all, with the publication of this issue, his years as editor of Paedagogica Historica are over. In a sense, therefore, the reflections brought here are somewhat his spiritual testament, even if this is put into perspective from the outset by the author himself. Indeed, the article reiterates some positions already taken in the past, such as the idea that, by drawing "lessons" from the educational heritage, the discipline of history of education need not necessarily be made more relevant and/or topical in order to reclaim its place in the training of teachers and pedagogues. Rather, Depaepe argues in this context for staying in line with cultural-historically conceived research on educational history, even if this marginalises the discipline even more at the expense of so-called more efficient study domains. Nevertheless, the message proclaimed here remains, all in all, hopeful. Only insights on the basis of pedagogical historiography can sufficiently open the way to nuance and put into perspective contemporary discussions, debates, disagreements, tensions, conflicts and so on. That is why Depaepe ends on a positive note. In his words, "hope and realism: it seems old-fashioned, but unfortunately, in all these years I have not found better tools for a respectful, sincere and unbiased approach to the educational past".